PERFORMANCE OF TOMATO (LYSOPERSICON ESCULENTUM) GERMPLASMS GROWN IN BANGLADESH FOR SALINITY TOLERANCE MPLASM - Md. Alamgir Siddiky; Md. Shahabuddin Khan; Md. Mostafizur Rahman; Md Khabir Uddin (AGRIVITA, Journal of Agricultural Science, 2014)
A solution culture experiment was conducted to screen out a number of Bangladeshi tomato germplasms for salinity tolerance by exposed to control, 8, 12 dS/m NaCl (salt stress). Salinity tolerance of tomato germplasms were evaluated with respect to salinity tolerance index, shoot and root dry matter production, shoot Na+, K+, Ca2+ accumulation and their respective ratios. A tolerance index was calculated for every single germplasm in root, stem and leaf dry weights and in the K/Na and Ca/Na parameters of these organs. Tomato germplasms responded differently to salt tolerance. Based on the salinity tolerance index caused by the NaCl treatment “BT14 (BARI Tomato 14)” and “BHT5 (BARI Hybrid Tomato 5)” were found to be most tolerant germplasms to salinity with highest salinity tolerance index, root-shoot dry matter production, accumulation of K and Ca and exclusion of Na. Thus, “BT14” and “BHT5” can be regarded as a breeding material for development of new tomato varieties for tolerance to salinity.Key words: Tomato germplasms, salinity, tolerance index, dry matter, Ion concentration